Citraan dalam Kumpulan Sajak Rikyuu Hyakushuu - Hidayat, Ramadhani Firdaus; Suryawati, Cicilia Tantri (Universitas Airlangga, 2023)
Abstract This article aims to analyze the imageries and philosophies encapsulated within the collection of poems Rikyuu Hyakushuu by Sen no Rikyuu. Imagery is a literary technique that allows poets to describe concepts, feelings, or experiences in a more visual and immersive way. The approach employed is qualitative with a descriptive analysis method. The data analyzed is extracted from the book Rikyuu Douka ni Manabu authored by Abe Sosei and published by Tankousha in 2000 in Kyoto. The analysis revealed that the most prevalent imageries in the poetry are visual imagery, followed by kinetic, emotional, olfactory, and auditory imageries. Each type of imagery correlates with various aspects of the chanoyu practice (Japanese tea ceremony). Furthermore, the scrutiny of chanoyu's philosophical aspects like wa (harmony), kei (respect), sei (cleanliness), and jaku (tranquility) in each type of imagery demonstrates that visual imageries embody wa and sei, auditory imageries embody kei, kinetic imageries embody kei and sei, olfactory imageries embody sei, and emotional imageries predominantly embody jaku and kei values.